Produksi Film Dokumenter Kain Tenun Ikat Sumba Timur dengan Menggunakan Teknik Sinematografi Extreme Close-Up - Jonathan Febrian Lius (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
East Sumba has a great potential for natural and cultural tourism. Currently, East Sumba is one of the potential tourist attractions that appeals for both domestic and foreign tourists to come and visit the region of East Nusa Tenggara, particularly Sumba Island. In addition to natural tourism, East Sumba also possesses an iconic commodity that is also an ancestral heritage, which is the kain tenun ikat woven fabric of East Sumba. With currently existing technologies, people have become more facilitated in seeking information. In a documentary video, the angle of shooting utilized the extreme close-up cinematography technique in certain parts of the creation process for the kain tenun. The shooting of the film with the extreme close-up technique is expected to be able to bring out or enhance the details of the creation process for the kain tenun ikat of East Sumba. The documentary film that shows the process of making the kain tenun ikat of East Sumba is expected to become a film that can engage the interests of youths and local tourists to learn about and participate in preserving the cultural heritage of the kain tenun ikat from East Sumba.